Optimalisasi Manajemen Hospitality Berbasis Pelayanan Prima melalui Penataan SDM di Klinik Haji Mabar Kota Medan - Ayulita Ramadhani; Devana Anisha Indra Putri; Farianita Lestar; Alwi Ihsan Nababan; Haryaji Catur Putera Hasman; Berry Dhiyashavana (CERED Indonesia Publishing, 2026)
This community service aims to strengthen the healthcare hospitality support system through education and the implementation of integrated Human Resources (HR) management at Klinik Haji Mabar, Medan City. The novelty of this program lies in its structural upstream approach, utilizing HR administration and competency tracking systems as the fundamental prerequisite to guarantee a consistent hospitality culture, rather than merely focusing on downstream patient interactions. The activity was conducted using a participatory approach comprising four stages: problem identification, material and system design, empathetic communication training and simulation, and implementation mentoring, involving 15 healthcare and administrative staff members. Evaluation results demonstrated a significant 34.97% increase in participants' cognitive understanding, with the average pre-test score (53.61) rising to 88.58 in the post-test. Managerial outputs, including Standard Operating Procedures (SOP) for hospitality service flow and a digitized ordner-based HR archiving system, were successfully implemented. In conclusion, comprehensive HR management structuring interventions are proven to be highly effective in accelerating the capacity of clinic staff to consistently deliver responsive, empathetic, and humanistic excellent service for BPJS Health participants.